Colony Growth Rate and Morphological Characterization of Bovine Rumen Bacteria in Fermented Liquid - Irawan, Triono Bambang; Kusuma, Indra Satria; Soelaksini, Liliek Dwi; Nuraisyah, Anni (META: Journal of Science and Technological Education, 2024)
Bovine rumen bacteria consist of diverse microorganisms essential for processing manure, compost, and liquid organic fertilizer, enhancing soil fertility and nutrient availability while suppressing pests and pathogens. These bacteria include cellulose-digesting species such as Bacteroides succinogenes, Ruminococcus flavefaciens, and Ruminococcus albus, which produce cellulase enzymes for organic matter decomposition. Morphologically, cellulolytic bacteria are categorized into coccus forms (Ruminococcus flavefaciens and Ruminococcus albus) and rod forms (Bacteroides succinogenes and Butyrivibrio fibrisolvens), with Gram-positive and Gram-negative cell walls. This study examined the growth and morphology of bovine rumen bacteria in fermented liquid over three weeks. Colony counts increased from 4.75 × 10⁶ CFU/mL in week 1 to 2.92 × 10⁷ CFU/mL in week 2 and 6.2 × 10⁸ CFU/mL in week 3. Colony morphologies included colors (pink, yellow, blue center), sizes (small, medium, large), shapes (circular, irregular), elevations (raised, convex, unbonated), surfaces (smooth, mucoid), and edges (regular, irregular). Predominant bacterial cell shapes were bacillus, with Gram-positive staining. These findings underscore the potential of bovine rumen bacteria in organic waste fermentation and nutrient cycling.